The role of aTp-dependent chromatin remodeling factors in chromatin assembly in vivo - Iu. A. Il’ina; A. Yu. Konev (Вавиловский журнал генетики и селекции)
Chromatin assembly is a fundamental process essential for chromosome duplication subsequent to DNA replication. In addition, histone removal and incorporation take place constantly throughout the cell cycle in the course of DNA-utilizing processes, such as transcription, damage repair or recombination. In vitro studies have revealed that nucleosome assembly relies on the combined action of core histone chaperones and ATP-utilizing molecular motor proteins such as ACF or CHD1. Despite extensive biochemical characterization of ATP-dependent chromatin assembly and remodeling factors, it has remained unclear to what extent nucleosome assembly is an ATP-dependent process in vivo. Our original and published data about the functions of ATP-dependent chromatin assembly and remodeling factors clearly demonstrated that these proteins are important for nucleosome assembly and histone exchange in vivo. During male pronucleus reorganization after fertilization CHD1 has a critical role in the genomescale, replication-independent nucleosome assembly involving the histone variant H3.3. Thus, the molecular motor proteins, such as CHD1, function not only in the remodeling of existing nucleosomes but also in de novo nucleosome assembly from DNA and histones in vivo. ATP-dependent chromatin assembly and remodeling factors have been implicated in the process of histone exchange during transcription and DNA repair, in the maintenance of centromeric chromatin and in the loading and remodeling of nucleosomes behind a replication fork. Thus, chromatin remodeling factors are involved in the processes of both replication-dependent and replication-independent chromatin assembly. The role of these proteins is especially prominent in the processes of large-scale chromatin reorganization; for example, during male pronucleus formation or in DNA repair. Together, ATP-dependent chromatin assembly factors, histone chaperones and chromatin modifying enzymes form a “chromatin integrity network” to ensure proper maintenance and propagation of chromatin landscape.